2014
DOI: 10.3892/ijmm.2014.1846
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of osteoclast bone resorption activity through osteoprotegerin-induced damage of the sealing zone

Abstract: Bone remodeling is dependent on the dynamic equilibrium between osteoclast-mediated bone resorption and osteoblast-mediated osteogenesis. The sealing zone is an osteoclast-specific cytoskeletal structure, the integrity of which is critical for osteoclast-mediated bone resorption. To date, studies have focused mainly on the osteoprotegerin (OPG)‑induced inhibition of osteoclast differentiation through the OPG/receptor activator of the nuclear factor kappa-B ligand (RANKL)/RANK system, which affects the bone res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…To date, studies have focused mainly on the OPG-induced inhibition of osteoclastogenesis through the RANKL/RANK system [37]. However, recently, Song et al [38] have demonstrated that OPG had directly affect osteoclastogenesis inhibiting the expression of critical genes involved in osteoclast maturation. Hence, we speculate that in our experiment in the absence of its ligand, OPG could explain its direct inhibitory function, acting in supplementation to OPG levels in IFN-γ stimulated-OC supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have focused mainly on the OPG-induced inhibition of osteoclastogenesis through the RANKL/RANK system [37]. However, recently, Song et al [38] have demonstrated that OPG had directly affect osteoclastogenesis inhibiting the expression of critical genes involved in osteoclast maturation. Hence, we speculate that in our experiment in the absence of its ligand, OPG could explain its direct inhibitory function, acting in supplementation to OPG levels in IFN-γ stimulated-OC supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…OPG is also produced by cells of osteoblastic lineage, and is able to inhibit the differentiation of macrophages into osteoclasts (9,11). To verify the hypothesis that the differentiation of RAW264.7 macrophages caused their apoptosis, OPG was added into the RANKL+M-CSF induction treatment group in order to inhibit the differentiation of RAW264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that in the presence of receptor activator of nuclear factor κB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF), osteoclasts are able to be formed by the differentiation of several monocyte/macrophage precursors (1,(6)(7)(8). Osteoclast differentiation and bone resorption is mainly regulated by osteoprotegerin (OPG)/RANKL/receptor activator of nuclear factor κB (RANK) system (9)(10)(11), in which RANKL and OPG are secreted by osteoblasts (4,12). RANKL binds to its receptor activator RANK in the osteoclast precursors, thereby inducing the differentiation of macrophages into osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…The results of OPG expression showed that PBM group had greater OPG expression on both sides of compression and tension compared to the conventional treatment group. OPG has been linked to the inhibition of osteoclastogenesis during root resorption through the OPG/RANKL/RANK pathway, damaging the sealing zone of osteoclasts or inducing apoptosis of osteoclasts and osteoclast precursor cells . However, Yu et al .…”
Section: Discussionmentioning
confidence: 99%